Curriculum Enhancement and Language Assessment in Pesantren: Examining Arabic Oral and Written Tests at Pondok Modern Darussalam Gontor Putri Campus 1 - Fairuz Subakir Ahmad; Agus Yasin; Ahmad Ario Sofian; Nur Fera Khalifah; Nuraeni Rahmawati (AFKARINA: Jurnal Pendidikan Agama Islam, 2024)
This study examines the implementation of Arabic oral and written examinations and their contribution to curriculum enhancement at Pondok Modern Darussalam Gontor Putri Kampus 1. Using a qualitative case study approach, data were collected through observations, semi-structured interviews, and document analysis involving Arabic teachers, curriculum coordinators, language supervisors, and students. The findings reveal that oral and written assessments function not only as evaluative instruments but also as strategic mechanisms for strengthening communicative competence, academic literacy, language discipline, and institutional language culture. Oral examinations reinforce students’ speaking fluency, confidence, and spontaneous communication skills through authentic interaction, while written examinations develop grammatical mastery, reading comprehension, analytical thinking, and academic writing proficiency. Furthermore, assessment outcomes are systematically utilized as feedback for curriculum refinement, instructional improvement, vocabulary reinforcement, and extracurricular language programs. The study demonstrates that Arabic language assessment in pesantren education reflects a holistic and competency-based curriculum model integrating cognitive, communicative, and behavioral dimensions of language learning. This research contributes theoretically to the discourse of Arabic language assessment and practically offers implications for developing authentic, integrative, and sustainable assessment systems in Islamic educational institutions.